An Extended Grain‐Based Model for Characterizing Crystalline Materials: An Example of Marble. Issue 8 (26th June 2018) - Wong, Louis Ngai Yuen; Zhang, Yahui
Abstract: An extended grain‐based model (EGBM) is proposed with the purpose of explicitly incorporating morphological and metric characteristics of the crystalline structure for realistic simulation of crystalline materials. The objectives of this paper are twofold: (a) to improve the Voronoi grain‐based model (VGBM), and (b) to discuss several key challenges associated with model calibration. The EGBM is realized using the software Particle Flow Code (PFC) based on the principle of VGBM. To determine a representative EGBM, a simple calibration procedure taking the microcracking process into account is suggested. Using a crystalline rock as an example, three EGBMs with different rock structures as well as a conventional bonded‐particle model (BPM) have been examined to study the effect of geometric heterogeneity on physico‐mechanical behavior. The geometric heterogeneity of the three EGBMs is quantified by the geometric deviation index, which measures the standard deviation of fractal dimensions of the constitutive mineral grains. Simulation results suggest that: (1) BPM has very different microcracking mechanism from GBM owing to their different model formulations; (2) increasing irregularity of grain shape promotes the opening and sliding of grains along their boundaries; and (3) fracture complexity increases with increasing geometric heterogeneity. Abstract : Crystalline microstructures are mostly numerically simulated using statistical approaches. An extended grain‐based model is developed to capture the influences of realistic crystalline morphology on the physico‐mechanical behavior of the material. A simple calibration procedure and a geometric deviation index are proposed to determine input model parameters and to assess the geometric heterogeneity of the simulated material, respectively.